Is increased fat content of hindmilk due to the size or the number of milk fat globules? - Itabashi Kazuo; Mukai Yoshiharu; Murase Masahiko; Taki Motohiro; Nishida Yoshiko; Mizuno Katsumi; Debari Kazuhiro; Iiyama Ai (BMC, 2009)
Abstract Background It is known that the fat content of breast milk is higher in hindmilk than in foremilk. However, it has not been determined if this increased fat content results from an increase in the number of milk fat globules (MFGs), an increase in the size of MFGs, or both. This study aims to determine which factor plays the most important role. Methods Thirteen breastfeeding mothers were enrolled in the study and we obtained 52 samples from 26 breasts before (foremilk) and after (hindmilk) a breastfeeding session. The fat content was evaluated by creamatocrit (CrCt) values. MFG size was measured with the laser light scattering method. We compared CrCt values and MFG size between foremilk and hindmilk. Results Although the CrCt values were higher in the hindmilk (8.6 ± 3.6%) than in the foremilk (3.7 ± 1.7%), the MFG size did not change (4.2 ± 1.0 μm and 4.6 ± 2.1 μm, foremilk and hindmilk, respectively). There was no relationship between the changes in CrCt versus MFG size from foremilk to hindmilk. Conclusion The results indicate that the increase in fat content results mainly from the increased number of MFGs, which may be released into the milk flow as the mammary lobe becomes progressively emptied.